Endoscopy in surgery - Rodríguez-Luna, María Rita; Perretta, Silvana (Frontiers in Gastroenterology, 2023)
The expanding role of flexible endoscopy (FE) has helped to establish better diagnostic strategies and fewer invasive therapies within the lumen of the gastrointestinal (GI) tract. Endoscopic skills represent critical tools for surgeons since they markedly impact perioperative outcomes. Although it is widely recognized that endoscopy plays a key role in digestive surgery, endoscopic curricula and syllabi may vary depending on geographical regions, which have their own standardized guidelines such as the United States and countries with numerous disparities such as Western Europe. Such heterogeneous practices represent a call for action, particularly as surgical societies aim to expand cutting-edge endoscopy within surgery. This article outlines the crucial role of intraoperative endoscopy in commonly performed digestive surgeries and stresses the need to develop standardized endoscopic training curricula in surgery, particularly in Europe.